2018
DOI: 10.1016/j.psym.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Illness in Takotsubo (Stress) Cardiomyopathy: A Review

Abstract: There is a strong association between pre-existing psychiatric illness, particularly anxiety and mood spectrum disorders, and TC. Acute exacerbation of psychiatric illness, rapid uptitration or overdose of certain psychotropic agents, and electroconvulsive therapy may trigger TC. Further studies are needed to better evaluate the prognostic significance and long-term management of psychiatric illness in TC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…Depression and anxiety have been associated not only with TTS (Nayeri et al, 2018), but also with elevated risk of developing other cardiac diseases (Janszky et al, 2007;Kendler et al, 2009;Gustad et al, 2014;Galli et al, 2017). A recent retrospective cohort study (Nayeri et al, 2018) found that preexisting psychopathologic disorders (anxiety, mood disorders, and schizophrenia) were associated with an increased risk of recurrent TTS, but not to survival. It is well recognized that the comorbidity of anxiety and depression is more the rule than the exception in many chronic disorders (Fava et al, 2012;Nayeri et al, 2017) including cardiac diseases (Bahremand et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety have been associated not only with TTS (Nayeri et al, 2018), but also with elevated risk of developing other cardiac diseases (Janszky et al, 2007;Kendler et al, 2009;Gustad et al, 2014;Galli et al, 2017). A recent retrospective cohort study (Nayeri et al, 2018) found that preexisting psychopathologic disorders (anxiety, mood disorders, and schizophrenia) were associated with an increased risk of recurrent TTS, but not to survival. It is well recognized that the comorbidity of anxiety and depression is more the rule than the exception in many chronic disorders (Fava et al, 2012;Nayeri et al, 2017) including cardiac diseases (Bahremand et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The spasm is induced by a sudden catecholamine increase since patients with takotsubo cardiomyopathy have elevated catecholamine blood concentrations. Takotsubo cardiomyopathy was also strongly associated with mental illnesses (19). Although our patient did not undergo angiography, we find takotsubo cardiomyopathy a more likely diagnosis than ST-elevation myocardial infarction for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…There are three reports on the concomitant use of beta blockers in patients who develop takotsubo cardiomyopathy, similar to our case (5,7,12). Patients may be predisposed to develop takotsubo cardiomyopathy by conditions that raise baseline catecholamine level (17,19). Both caffeine and nicotine elevate catecholamine blood levels (25), and our patient’s caffeine and nicotine use could have precipitated a cardiovascular accident.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this result can be explained by looking at the greater prevalence of psychiatric diseases, primarily anxiety, in patients with TTS in this study. Moreover, to date, there have been no clear cases of SSRIs as triggers of TTS [44].…”
Section: Psychoactive Drugsmentioning
confidence: 99%